2018
DOI: 10.1039/c7dt03962j
|View full text |Cite
|
Sign up to set email alerts
|

Light-initiated reversible conversion of macrocyclic endoperoxides derived from half-sandwich rhodium-based metallarectangles

Abstract: Although reversible photo-dimerization or oxygenation of anthracene and its derivatives is a common reaction, light-initiated reversible conversion of endoperoxide organometallic frameworks has only rarely been addressed. Herein, a series of tetranuclear organometallic macrocycles, [Cp*Rh(μ-CO-κO)](BP4VA)(OTf) (4), [Cp*Rh(BiBzIm)](BP4VA)(OTf) (5), and [Cp*Rh(DHBQ)](BP4VA)(OTf) (6), were obtained in good yields from the reactions of the binuclear half-sandwich rhodium precursors [Cp*Rh(μ-CO-κO)Cl] (1), [Cp*Rh(B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…1 month. However, leaving 4 in solution for several days results in very broad resonances, implying decomposition, which is consistent with other endoperoxides. , …”
supporting
confidence: 81%
See 2 more Smart Citations
“…1 month. However, leaving 4 in solution for several days results in very broad resonances, implying decomposition, which is consistent with other endoperoxides. , …”
supporting
confidence: 81%
“…Many polyaromatic molecules, anthracene included, can “reversibly” bind singlet oxygen ( 1 O 2 ) to form endoperoxide groups. , There are few reported examples of endoperoxide macrocycles. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although many techniques like in situ NMR, mass spectroscopy, and electron paramagnetic resonance (EPR) could be available for the mechanism investigation, it is still a tough job to acquire important information about the in situ formed intermediates, which are key to understanding the mechanism of organic reactions. Recently, metal–organic-frameworks (MOFs) have become one type of powerful structural materials which can be used as straightforward alternative tools for performing some organic reactions and capturing the in situ cleaved species within their frameworks. We also reported that the hydrothermal reaction of CdCl 2 with 1,3-benzene­dicarbox­ylic acid (1,3-H 2 bdc), 1,3-bis­(4′-pyridyl)­2,4-bis­(phenyl)­cyclobutane (HT-ppcb), and H 2 O 2 afforded one unique 2D MOF, {[Cd­(H 2 O)­(1,3-bdc)­(bpbpf)]·H 2 O} n (bpbpf = 2,4-bis­(4-pyridyl)-3,5-bis­(phenyl)­furan) . In this reaction, HT-ppcb was converted into bpbpf via the ring-opening of HT-ppcb, followed by in situ oxidation, which was trapped into this MOF.…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H diffusionordered spectroscopy (DOSY) NMR spectrum of 1 clearly indicated that these signals for the aromatic and Cp* units showed a single diffusion coefficient (2.38 × 10 −10 m 2 s −1 ), further confirming stable presence of structure 1 (Figure 3b). Moreover, the results of IR spectrum of complex 1 exhibits a strong band at 3441 cm −1 owing to the stretching vibration of the N-H bond of imidazole group [40][41][42], the peaks at 1030 and 1279 are likely the asymmetric and symmetric sulfonate stretches and the peaks at 1160 are due to CF 3 asymmetric and symmetric stretches [43][44][45]. The peaks at 1614 and 1444 are likely attributed to the vibration of aromatic ring structures of ligand L1 (Figure 4).…”
Section: Analysis Of Metallarectanglementioning
confidence: 96%